Tarjih maqasidi of Terrorism Perpetrators Death Penalty in Indonesia - Aprilianto, Dwi; Na'imah, Farida Ulvi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2021)
Upload the death penalty for the perpetrators of terrorism that the government efforts to get a lot of doubt about its effectiveness. For the government, giving the death penalty to the perpetrators of terrorism makes other terrorism networks feel fear and a deterrent to doing the same. In some cases that exist so far, quite the opposite, the perpetrators of terrorism consider death through punishment for committing acts is an honor and heroism by the network community. Empirical research is processed descriptively. Data collection is carried out through field research at the Class I Surabaya Prison through a phenomenological approach, interpretive paradigm, and analysis tarjih{ maqa@s}idiy. The study concluded that the death penalty for terrorism is a more significant benefit (mas}lah}ah arjah}) than allowing the ideologists of terrorism who are still radicalized and without remorse with life sentences. Preventing the process of radicalism from ideologists takes precedence over taking and waiting for the indiscriminate benefit of the life of convicts who do not feel guilty.